Makna Toleransi Dalam Al-Qur’an dan Bibel (Analisis Intertekstualitas Julia Kristeva) - Wijaya, Roma (Universitas Islam Negeri Raden Mas Said Surakarta, 2022)
Indonesia has a variety of cultures, especially recognized religions, namely Islam, Protestantism, Catholicism, Hinduism, Buddhism, and Confucianism, which are the joint task of realizing mutual respect without hatred. Religion has a dual role and function that can be constructive and destructive. Constructively able to support humans to live in one unity, live steadfastly, harmoniously and peacefully. In contrast to the destructive nature of religion, it can lead to polemics for the destruction of unity and even break the ties of blood brotherhood which has an impact on a conflict with a religious background making it difficult to predict the outcome. . This paper describes the opinions of the two major religions in Indonesia, namely Islam and Christianity, which explore the meaning and principles of tolerance based on the Qur'an and the Bible. This type of research is qualitative. The theory used in this study applies Julia Kristeva's intertextuality theory. This theory will dialogue the meaning of tolerance that is in the construction of the verses of the Qur'an and the Bible. The results of this study will show the existence of a modified principle of the Qur'an which shows the concept of tolerance according to the historical context. Parallel principle which reveals the harmony of meaning of tolerance between the Qur'an and the Bible. The Qur'an forbids us to force others to enter. Religious tolerance according to Christianity is still conveying the truth of the teachings of Christian beliefs, but respecting the truths of other religions.